1998
DOI: 10.1007/pl00008161
|View full text |Cite
|
Sign up to set email alerts
|

Sources of timing variations in music performance: A psychological segmentation model

Abstract: Systematic timing variations observed during music performance have usually been attributed to a musical expression hypothesis, related to relatively highlevel processes, by which musicians emphasize certain events in order to transmit a particular musical interpretation to the listener. We propose, in addition, a perceptual hypothesis, related to lower-level processes, in which some observed variations would be related to functional constraints of the auditory system. (Some intervals would be heard shorter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 47 publications
6
59
0
Order By: Relevance
“…Drake and Palmer (1993) found that melodically accented notes were separated from the preceding notes by longer IOIs in the performance of simple sequences and real music. Penel and Drake (1998) replicated the finding in cases in which pitch jumps did not coincide with conflicting structural features. Repp (1992b) did not find a consistent relationship between pitch change and timing in musical performance.…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…Drake and Palmer (1993) found that melodically accented notes were separated from the preceding notes by longer IOIs in the performance of simple sequences and real music. Penel and Drake (1998) replicated the finding in cases in which pitch jumps did not coincide with conflicting structural features. Repp (1992b) did not find a consistent relationship between pitch change and timing in musical performance.…”
Section: Methodssupporting
confidence: 67%
“…Structural cognition is assumed to be under voluntary control, whereas auditory processing and structural perception are not (Repp, 1998). The fact that performers use some expressive variation even when they are instructed to perform mechanically (Drake & Palmer, 1993;Gabrielsson, 1974;Penel & Drake, 1998) indicates that structural cognition may be only partially responsible for the variations in perception and performance of music.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first computational model was presented by Todd (1985Todd ( , 1989; see also Windsor & Clarke, 1997;Penel & Drake, 1998) and accounted for the variation of measure duration over phrases. Todd later developed a revised model based on a different mathematical function, which he argued was more closely related to a metaphor of physical motion (Todd, 1992(Todd, , 1995.…”
Section: Phrasingmentioning
confidence: 99%